2010
DOI: 10.3390/md8041153
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriocin as Weapons in the Marine Animal-Associated Bacteria Warfare: Inventory and Potential Applications as an Aquaculture Probiotic

Abstract: As the association of marine animals with bacteria has become more commonly recognized, researchers have increasingly questioned whether these animals actually produce many of the bioactive compounds originally isolated from them. Bacteriocins, ribosomally synthesized antibiotic peptides, constitute one of the most potent weapons to fight against pathogen infections. Indeed, bacteriocinogenic bacteria may prevent pathogen dissemination by occupying the same ecological niche. Bacteriocinogenic strains associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
76
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(94 citation statements)
references
References 141 publications
0
76
0
7
Order By: Relevance
“…Several studies suggest that production of bacteriocins and organic acids (mainly lactic acid) are the main weapons of probiotic LAB of fish and aquatic origin to fight against pathogens of relevance for aquaculture [61,62], similarly as reported for human and farm animals probiotic LAB [62,63]. With regard to this, from the 75 lactococci analyzed in this study, only 9 (12 %) strains were identified as bacteriocin producers.…”
Section: Discussionmentioning
confidence: 72%
“…Several studies suggest that production of bacteriocins and organic acids (mainly lactic acid) are the main weapons of probiotic LAB of fish and aquatic origin to fight against pathogens of relevance for aquaculture [61,62], similarly as reported for human and farm animals probiotic LAB [62,63]. With regard to this, from the 75 lactococci analyzed in this study, only 9 (12 %) strains were identified as bacteriocin producers.…”
Section: Discussionmentioning
confidence: 72%
“…In this study, the 8 P. acidilactici strains displayed a broad antimicrobial spectrum against fish pathogens, which could be due to different antimicrobial metabolites such as organic acids (mainly lactic acid), hydrogen peroxide, diacetyl, acetaldehyde, and/or bacteriocins, with the organic acids and bacteriocins being the key weapons in inhibiting pathogens of relevance for aquaculture (Gillor et al 2008, Desriac et al 2010. In this respect, 6 out of 8 P. acidilactici strains were found to be bacteriocin producers, based on the proteinaceous nature and heat stability of the antimicrobial agent, which is in agreement with previous studies, where a remarkably high number of LAB displaying antimicrobial activity against fish pathogens were potential bacteriocin producers (Muñoz-Atienza et al 2013, Gómez-Sala et al 2015.…”
Section: Discussionmentioning
confidence: 92%
“…Farming industries, such as the poultry industry [21,69] and aquaculture industry [70], look for more efficient ways to treat their stock. Interest in human applications comes from scientists and companies that realize the global health and economic potential of bacteriocin therapeutics.…”
Section: Discussionmentioning
confidence: 99%